Effect of seed treatment using Mancozeb and Ridomil fungicides on Rhizobium strain performance, nodulation and yield of soybean (Glycine max L.) - Getachew, Zerihun; Abeble, Lejalem (Journal of Agriculture and Natural Resources, 2021)
The viability of commercial Rhizobium strains (SB-14 and SB-12) were inoculated and fungicides (Mancozeb and Ridomil) were used as seed dressed on soybean seed to investigate their effect on nodulation, plant growth and seed yield of soybean. Application of Rhizobial inoculants alone gave the highest nodulation and shoot dry weight performance as well as seed yield of soybean on both sites. SB-12 inoculant had significantly shown to be more effective than SB-14 inoculant in increasing nodulation and thus produced higher plant growth and seed yield. Rhizobial survival on the seeds was severely affected by both fungicides, resulting in decreased nodulation, plant growth and seed yield for both inoculants. However, Ridomil fungicide gave the lowest nodulation and seed yield when applied with either SB-12 or SB-14 Rhizobial strains. The strains differed in their sensitivity to Mancozeb fungicide that with strain SB-12 showed a slight effect or no effect on survival of rhizobium, nodulation and yield of soybean. Seed-dressing of mancozeb and ridomil resulted in reduction of seed yield by 882.8 kg ha-1 and 1154.7 kg ha-1, respectively with SB-12 strain. The present results indicate that inoculated Rhizobium inoculants differ in their capacity to develop resistance to the two dressed fungicides. Seed treatment with Mancozeb in combination with SB-12 strain slightly affected the survival of the inoculated strain. Consequently, mancozeb fungicide may be compatable with survival of the inoculated SB-12 Rhizobia. The results also indicate that the suppressive effects of seed-applied fungicides on Rhizobium strains survival and nodulation development depend on specific strain and fungicide. Soybean seeds inoculated with SB-12 may not need management with fungicides or lower concentration of Mancozeb that could be compatible with SB-12 to suppress soil-borne pathogens for both Assosa and Begi sites, western Ethiopia.